Safety and Feasibility of Chemoembolization with Doxorubicin-Loaded Small Calibrated Microspheres in Patients with Hepatocellular Carcinoma: Results of the MIRACLE I Prospective Multicenter Study - Richter, Götz; Radeleff, Boris; Stroszczynski, Christian; Pereira, Philippe; Helmberger, Thomas; Barakat, Mark; Huppert, Peter (CardioVascular and Interventional Radiology, 2018)
Purpose The MIRACLE I pilot study was designed as a preliminary investigation of safety and efficacy of Embozene TANDEM microspheres loaded with doxorubicin for treatment of locally untreatable (i.e., unresectable and not suitable for local thermal ablation) hepatocellular carcinoma (HCC). Materials and Methods Patients with locally untreatable HCC (mono- or bilobar disease, ECOG performance status 0–2, Child–Pugh score < 11) were eligible for this single-arm multicenter study. DEB-TACE was performed with 75 µm Embozene TANDEM loaded with 150 mg of doxorubicin. Results Twenty-five subjects with 41 tumors were treated (mean age 65 years); 16, 52, and 32% had BCLC A, B, and C status, respectively. Child–Pugh status was A for 64%, B for 32%, and C for 4%; 40% had ascites. About 92% had disease localized to one liver lobe. Most (72%) underwent ≤ 2 DEB-TACE procedures. Average doxorubicin dose was 124.5 ± 36.1 mg (median 150 mg) per procedure. Two patients had procedure-related SAE (liver necrosis, worsening of liver insufficiency) within 30 days of the first DEB-TACE procedure. Six-month freedom from procedure-related SAE or death was 68% (one hepatic encephalopathy, five deaths). Tumor response or stable disease was achieved in 95% (20/21) of subjects. Freedom from tumor progression or death at 6 months was 76%. The one-year survival rate was 56% overall and 73% among patients without ascites at baseline. Conclusion MIRACLE I results suggest that Embozene TANDEM microspheres loaded with doxorubicin can provide good local tumor control in a heterogeneous group of patients with locally untreatable HCC. Level of Evidence Level 2b, Individual cohort study.